Over-the-counter medication patterns in households in Sharjah, United Arab Emirates - Zaghloul AA; Elsergany M; El-Enein NA; Alsuwaid H; Ayoub M (Dove Medical Press, 2013)
Ashraf Ahmad Zaghloull,1 Moetaz Elsergany,2 Nagwa Abou El-Enein,1 Hamda Alsuwaidi,3 Mohamed Ayoub3 1Health Administration and Behavioral Sciences Department, High Institute of Public Health, University of Alexandria, Alexandria, Egypt; 2e-School Health and Environmental Studies, Hamdan Bin Mohamed eUniversity, Dubai, United Arab Emirates; 3College of Health Sciences, University of Sharjah, United Arab Emirates. Background: Self-medication and acquisition of over-the-counter (OTC) medications are emerging community health issues. Besides being a cheap alternative for treating common illnesses, the behavior entails serious ramifications, such as medication wastage, increasing pathogen resistance, and adverse drug reactions. The present study was conducted to explore the extent of OTC medications in households in Sharjah, United Arab Emirates (UAE), including native UAE and expatriate families. Methods: The study employed a population-based, cross-sectional, analytical study design. The study population included native and expatriate households residing in the Emirate of Sharjah, UAE. The snowball sampling technique was used, and the sample included a total of 335 households. Results: Expatriate households acquired more OTC medications than did native households (adjusted odds ratio [aOR]=1.7). The demographic determinants for expatriate households were number of family members (aOR=1.6), age of children in the family (aOR=1.8), and annual income (aOR=0.5). Expatriate households purchased more OTC medication practices than did native households (aOR=2.2). In the statistical sense, expatriate household practices were buying medication upon relatives' advice (aOR=0.3), storage condition of medication (aOR=2.4), and disposal of expired medication (aOR=0.6). The highest percentages of OTC medications in native and expatriate households were those related to gastric and ear, nose, and throat illnesses. Conclusion: The presence of OTC medications in expatriate households was two-fold more common than in native households in Sharjah, UAE. There were significant associations for behaviors related to the reasons why OTC medications were purchased and stored within the household for both native and expatriate families. Keywords: over-the-counter medication, pattern, odds ratio, household, Sharjah